2020
DOI: 10.1002/chem.201904415
|View full text |Cite
|
Sign up to set email alerts
|

Exciplex Formation and Electromer Blocking for Highly Efficient Blue Thermally Activated Delayed Fluorescence OLEDs with All‐Solution‐Processed Organic Layers

Abstract: Highly efficient solution‐processable emitters are greatly desired to develop low‐cost organic light‐emitting diodes (OLEDs). The recently developed thermally activated delayed fluorescence (TADF) materials are promising candidates, but blue TADF materials compatible with the all‐solution‐process have still not been achieved. Here, a series of TADF materials, named X‐4CzCN, are developed by introducing the bulky units through an unconjugated linker, which realizes high molecular weight to enhance the solvent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…[ 27,28 ] However, the high device efficiencies of AIDF emitters are mainly achieved by vacuum deposition method, which generally is high‐cost and unfavorable for large area preparation. [ 29 ] As a contrast, solution‐process method has the advantage of low cost and large‐area preparation, while the performance of solution‐processed device mostly is disappointing. [ 30,31 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 27,28 ] However, the high device efficiencies of AIDF emitters are mainly achieved by vacuum deposition method, which generally is high‐cost and unfavorable for large area preparation. [ 29 ] As a contrast, solution‐process method has the advantage of low cost and large‐area preparation, while the performance of solution‐processed device mostly is disappointing. [ 30,31 ]…”
Section: Introductionmentioning
confidence: 99%
“…[27,28] However, the high device efficiencies of AIDF emitters are mainly achieved by vacuum deposition method, which generally is high-cost and unfavorable for large area preparation. [29] As a contrast, solution-process method has the advantage of low cost and large-area preparation, while the performance of solution-processed device mostly is disappointing. [30,31] Inspired by the core-shell structure in nature, herein, we proposed and designed a molecular core-shell structure by introducing flexible-chain linked bulk fragments as a shell layer to protect the core emitter for electroluminescence device.…”
Section: Introductionmentioning
confidence: 99%
“…Following an increase in the concentration of Py-B2An , the proportion of the extra two new peaks increased, and the peak at 552 nm was strongest at the concentration of 100%. According to the variation of the EL spectra along with increasing concentration, and considering the relatively coplanarity characteristic of Py-B2An as well as the anthracene-side group, for the extra two peaks, we speculate that they possibly originated from its excimer emission (552 nm), 62 and electromer emission 63 or the excimer emission of anthracene (524 nm), 64 respectively.…”
Section: Resultsmentioning
confidence: 88%
“…It has been reported that these dissociated free charges can be combined in additives and reused by transferring energy to the perovskites, which is a positive effect for the device efficiency of the quasi-2D perovskite LED. However, most of these additives follow the traditional fluorescence mechanism, which means only 25% singlet energy can be used for exciton retrieving. Recently, our group has designed and synthesized a series of thermal-activated delayed fluorescence (TADF) dendrimers for highly efficient solution-processed OLEDs. , These TADF materials not only have good film forming ability but also can suppress the concentration-quenching effect by its self-encapsulation . Using such a type of TADF material as an additive, the retrieved excitons can be 100% useful due to the efficient reverse intersystem system crossing from triplet to singlet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has designed and synthesized a series of thermal-activated delayed fluorescence (TADF) dendrimers for highly efficient solution-processed OLEDs. 35,36 These TADF materials not only have good film forming ability but also can suppress the concentrationquenching effect by its self-encapsulation. 37 Using such a type of TADF material as an additive, the retrieved excitons can be 100% useful due to the efficient reverse intersystem system crossing from triplet to singlet.…”
Section: Introductionmentioning
confidence: 99%